Sexual Abuse Among Adolescents - Udigwe IB; Ofiaeli OC; Ebenebe JC; Nri-Ezedi AC; Ofora VC; Nwaneli EI (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Adolescence constitutes a vulnerable age group where the actual prevalence of sexual abuse may remain largely unknown due to lack of knowledge, delay in and lack of reporting of such incidences. Objectives: To determine the knowledge and history of sexual abuse in adolescents and the associated factors. Methods: A self-administered pretested questionnaire was used to collect data from children aged 10 to 19 years at an adolescent summer camp. Results: Two hundred and seventy-six adolescents participated in this research out of which 41.3% had correct knowledge of sexual abuse, and 12.0% claimed they had been sexually abused. Among the 33 respondents with a history of sexual abuse, 39.4% (13/33) had correct knowledge of sexual abuse. Gender had a significant association with a history of sexual abuse (p = 0.008). Layered by age group, gender had a significant association with being sexually abused in mid-adolescence (p = 0.029) but not in late adolescence (p = 0.445). Age category had no significant association with being sexually abused. Conclusion: The knowledge of sexual abuse was inadequate among adolescents. A high proportion claimed to have been previously sexually abused and interestingly, had insufficient knowledge of sexual abuse There is a need to educate adolescents on sexual abuse to empower them to protect themselves and get help as appropriate.